Kesesuaian ANALISIS KESESUAIAN MINAT BAKAT SISWA DENGAN PRESTASI NON AKADEMIK (STUDI KASUS DI MI ALAM ANANDA MANDIRI SLAWI) - Falih, Muhammad Akmal (MEDIA DIDAKTIKA, 2024)
This study analyzes the suitability of MI students' interests, talents and non-academic achievements. This research was conducted at Madrasah Ibtidaiyah Alam Ananda Mandiri Slawi, with the aim of determining the extent to which students' interests and talents contribute to their non-academic achievements. This research uses a qualitative research approach. During the data collection process, this research used observation, interview and documentation methods. Based on the results, each child has different talents, interests and abilities in their own capacity, so the success of students can depend on improving their talents and skills. in the future.